Implementasi Prinsip Syariah dalam Pembiayaan Bank Syariah di Sulawesi Selatan: Implementasi Prinsip Syariah Dalam Pembiayaan Bank Syariah di Sulawesi Selatan - anwar, Rahma; Hijrawati; lmi Ayu Melani; Kamaruddin (STEI Kanjeng Sepuh Gresik Jawa Timur, 2025)
Islamic banking has emerged as a significant player in the financial landscape of South Sulawesi, contributing to both economic and social development. The implementation of sharia principles in banking practices has enabled these institutions to provide financial services that are not only profitable but also ethically aligned with community values. By focusing on micro, small, and medium enterprises (MSMEs), Islamic banks facilitate access to capital through various financing schemes such as mudharabah and murabahah, which adhere to Islamic law. This approach not only enhances the production capacity of local businesses but also fosters economic resilience in the region. Furthermore, Islamic banks actively engage in social investment through sharia-compliant corporate social responsibility (CSR) initiatives, addressing critical areas such as education and health. These efforts contribute to improving the overall quality of life for communities in South Sulawesi. The synergy between financial services and social responsibility highlights the multifaceted role of Islamic banks in promoting sustainable development. As such, the impact of Islamic banks extends beyond mere financial transactions; it encompasses a broader commitment to community empowerment and socio-economic progress.